(untitled) (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Biological Sciences Series, 2025)
A field experiment was carried out at the Bouqa farm affiliated to the Faculty of Agricultural Engineering at Lattakia University, during the agricultural seasons of 2019 and 2020, by planting a strain of triticale (Tcl1) in experimental plots individually and in mixtures with common vetch Vicia sativa L. according to three mixing ratios: 75% triticale and 25% vetch, 50% triticale and 50% vetch, and 25% triticale and 75% vetch. The aim of the research was to study the effect of mixing ratios of triticale with vetch on some morphological traits and harvest and threshing indices of triticale, grain and seed yield, and biological yield of the mixture. The experiment was carried out according to a Randomized Complete Block Design (RCBD). The research used a strain of triticale X. triticosecale wittmack (Tcl1) from the the General Commission for Scientific Agricultural Research, where it was selected based on the results of the previous season’s experiments in terms of its biological and grain yield. The strain is characterized by its relatively high yield (grain and biological), in addition to a forage legume crop: vetch Vicia sativa L.. The results indicated the effect of mixed cultivation in terms of the mixing ratio significantly in all the studied traits. Triticale outperformed in single cultivation (T%100) and when planted with vetch at a mixing ratio (T%75+V%25) compared to its other mixing treatments in terms of spike holder length, spike length, ear length, harvest index, and number of spikelets per spike during the two study seasons. Triticale grown individually was superior in terms of biological mixture yield and seed grain mixture yield, followed by the mixture (T%75+V%25) which was significantly superior to the other mixing treatments. We suggest planting fodder mixtures consisting of 75% triticale and 25% vetch in order to obtain the highest seed and grain yield and the highest biological yield.